'Heroes and Matriarchs': Working‐Class Femininities, Violence and Door Supervision Work. Issue 6 (5th November 2012) - Rickett, Bridgette; Roman, Andrew
<x xml:space="preserve">Abstract</x> Door supervision work is traditionally seen as a working‐class, male‐dominated trade. In addition, it is deemed to be one that is physically risky, where violence is seen as a 'tool of the trade' and where 'bodily capital' and 'fighting ability' are paramount to the competent performance of the job. This paper is a timely analysis on the manner in which the increasing numbers of women who work in door supervision negotiate their occupational identity and construct their work practices. The analysis focused on the way in which discursive constructions of both violence and workplace identities are variably taken up, reworked and resisted through the intersection of gender and class. This resulted in the identification of two main discourses; 'playing the hero' and the 'hard matriarch'. These findings allow us to theorize that multiple, gendered and classed occupational identities exist beyond normative expectations and can be seen to be both emancipatory for working women, while simultaneously bolstering exploitation, workplace harassment and violent practices.